Gender inclusivity in Finnish football social media: Investigating Finnish Football Association's Instagram - Rantamaa, Emma (2025)
Rantamaa, E. 2025. Gender inclusivity in Finnish football social media: Investigating Finnish Football Association's Instagram. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis, Responsible Management and Business of Sport, 76 pp.. 1 appendix.